THE EFFECT OF ORGANIZATIONAL CULTURE ON ORGANIZATIONAL SILENCE: MULTIPLE GROUP ANALYSIS ON DOMESTIC AND FOREIGN FIRM EMPLOYEES (Third Sector Social Economic Review, 2020)
The aim of the study is to examine the effect of culture types on organizational silence comparatively on the employees of international and local companies. Data were collected from 182 people working in Ankara and Antalya branches of two coffee brands, one with local and one with foreign capital, having branches across the country. The analyzes showed a negative relationship between clan culture and acquiescent and defensive silence, and a positive relationship between prosocial silence. Adhocracy, market and hierarchy culture has a significant and positive relationship with acquiescent and defensive silence, but negative with prosocial silence. Adhocracy culture has no significant effect on defensive silence. Hierarchy culture has no significant impact on acquiescent and prosocial silence. All other culture types have a significant effect on silence types. The effect of organizational culture types on organizational silence differ partially according to domestic and foreign company employees.
Keywords: Multi Group Analysis; Organizational Culture; Organizational Silence